A Corpus-based Study of Spanish Translations of the Verb ‘report’ in Biomedical Research Articles - Williams, Ian (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThis paper describes an empirical contextual study of the Spanish verbs that translate ‘report’ carried out on an extensive corpus of medical research articles. A quantitative analysis revealed significant differences between the lexical choices made by the translators and those made by native Spanish authors. The contextual analysis showed that reporting occurs in three basic settings, namely, the institutional setting, the community and patient setting, and the research setting. In the latter, research referred to the current study (i.e., the new clinical study presented in the article), to previous research by the same authors, or to other authors’ published work. Within these contexts, consideration of linguistic factors such as collocation, sentence structure and specific features of the communicative situation allows the translator to make the appropriate lexical choices for the wide range of uses of the polysemous English verb ‘report.’